2012
DOI: 10.1089/jpm.2011.0132
|View full text |Cite
|
Sign up to set email alerts
|

Practical Approaches toward Improving End-of-Life Care for People with Intellectual Disabilities: Effectiveness and Sustainability

Abstract: In general, the study found that there was a lack of understanding of each other's role between palliative care professionals and ID staff, with each unsure of what the other service is providing and how it is run. Recommendations include securing a development worker for ID and end-of-life care; conducting training for ID care staff; establishing how ID services are organized within the local area; linking to national training programs; ensuring that senior management is proactively involved; and ensuring tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…2,4,[11][12][13] However, a previous study has shown that willingness for these two services to collaborate was not enough to make it happen. 6 It is recognised that interdisciplinary education is an antecedent to collaborative working 14,17 and the limited uptake of professional education in this area of practice needs to be addressed. 14 At a human level, it was also clear from the findings that working together required a relationship of mutual trust and respect.…”
Section: Connecting and Enabling Partnershipmentioning
confidence: 99%
See 3 more Smart Citations
“…2,4,[11][12][13] However, a previous study has shown that willingness for these two services to collaborate was not enough to make it happen. 6 It is recognised that interdisciplinary education is an antecedent to collaborative working 14,17 and the limited uptake of professional education in this area of practice needs to be addressed. 14 At a human level, it was also clear from the findings that working together required a relationship of mutual trust and respect.…”
Section: Connecting and Enabling Partnershipmentioning
confidence: 99%
“…6 It is recognised that interdisciplinary education is an antecedent to collaborative working 14,17 and the limited uptake of professional education in this area of practice needs to be addressed. 14 At a human level, it was also clear from the findings that working together required a relationship of mutual trust and respect. 24 Narratives from the interviews, and case scenarios, provided evidence that relationships, centred on trust and respect for each other's knowledge base and skills, could dispel fear and mistrust which may have been present possibly due to services working in isolation and lack of familiarity with their different roles and philosophies.…”
Section: Connecting and Enabling Partnershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent position papers in other countries highlight this paucity of information, as well as the gaps in service provision and research evidence 17–19. In England, one of the key barriers to people with LDs accessing palliative care services is the lack of understanding and training of the staff working with them 20. LD staff are often young, lacking in training and experience, while staffing levels are low and turnover is high.…”
Section: Introductionmentioning
confidence: 99%